Perancangan Sistem Informasi Akuntansi Persediaan Barang Dagang Pada Toserba Selamat Menggunakan Php Dan Mysql - Tiara Rahmasari (Labkat Press KA FTIK UNIKOM, 2019)
The purpose of this research is to find out the accounting information system of merchandise inventory used by Toserba Selamat. Toserba Selamat itself stands in retail. Retail is an activity involved in selling goods or services directly to consumers for personal use. This research method uses descriptive by looking for research related theories about the system of accounting information on merchandise inventory. Data collection used is observation and interview. The type of data used is quantitative data. The results of this study are expected to be able to find out information about merchandise inventory accounting information systems. The design of the merchandise inventory accounting information system uses the method of developing the Dynamic System Development Method system with 3 main stages (before the project, project life cycle and after the project) and 5 sub stages (feasibility studies, business studies, looping models, repetition of design and manufacture and application). The discussion of design research on inventory inventory accounting information systems is expected to facilitate convenience stores in making inventory reports and financial reports.